Estimation of physical workload of the low-back based on exposure variation analysis during a full working day among male blue-collar workers. Cross-sectional workplace study. (July 2018) - Jakobsen, Markus Due; Sundstrup, Emil; Brandt, Mikkel; Persson, Roger; Andersen, Lars L.
Abstract: This study aims to quantify physical workload of the low-back using exposure variation analysis (EVA) during a full working day among blue-collar workers with manual lifting tasks. One hundred and ten male employees (39 warehouse workers, 27 operators, 24 postal workers and 20 slaughterhouse workers) with manual lifting tasks from 12 workplaces participated. The workers performed standardized box lifts using 5, 10, 20 and 30 kg before and after a working day. Muscular activity of the low-back was measured throughout the working day using surface electromyography (sEMG). Corresponding sEMG-values for 0–30 kg lifts were identified using linear regression. EVA at exposure levels corresponding to "lifting periods" of [1-5, 5-10, 10-20, 20-30 and >30] kg in time intervals [0–0.5, 0.5–1, 1-2, 2-5, 5-10, >10] sec was computed. Back inclination was measured using tri-axial accelerometers. Compared to the other job groups, the operators' low-back muscles were exposed to more short duration "lifting periods" with varying loads and more frequent medium duration high load "lifting periods", respectively. The operators also worked more with their back inclined (>30°, >60°, and >90°) than the remaining job groups. Nonetheless, more than 41% of the workers performed heavy "lifting periods" that exceeded Danish lifting guidelines. This EVA demonstrates that almost half of the blue-collar workers were exposed to heavy low-back loading which puts them at risk of developing musculoskeletal disorders and low-back injury. Operators are, in particular, exposed to more short duration and medium duration "lifting periods" with varying load compared to warehouse-, postal- and slaughterhouse workers. Highlights: Many blue-collar workers perform heavy lifting that exceeds lifting guidelines. Operators perform particularly many short to medium duration lifts. Operators are exposed to more back inclination than other blue-collar workers. Exposure variation analysis is a feasible tool for identifying physical risk factors.